Pedagogical Device in front of Human Rights Memory Mechanisms in the City of Tunja (2016)
The historical memory is an important right of preuniversity students to explore the truth about human rights violations. Knowing the truth implies establishing the identity of authors and causes, facts and circumstances related to violations, in turn, it allows the approach to a reality as a right to remember.Thus, the truth is not reduced to the individual right of any direct victim or his relatives to know what happened, but it is a right that reaches society based on the knowledge of its history and that includes “the duty to remember” or “duty of memory”. The State must take measures guaranteeing non-repetition,preventing violations from reproducing, since for a people, knowledge of the history of their oppression belongs to their heritage and as such must be preserved.